Testing Model Structure Through a Unification of Some Modern Parametric Models of Creep: An Application to 316H Stainless Steel - Mark Evans (Metallurgical and Materials Transactions A, 2020)
It is important to be able to predict the creep life of materials used in power plants and in aeroengines. This paper develops a new parametric creep model that extends those put forward by Wilshire and Yang et al. by having them as restricted or special cases of a new generalized model. When this generalized model was applied to failure time data on 316H stainless steel it was found that neither of these established parametric models explained the greatest variation in the experimentally obtained times to failure. Instead, a version of this generalized model was most compatible with the experimental data. It was further found that the activation energy for this material changed at a normalized stress of 0.41 due to a change from the domination of dislocation movement within grains to movement within grain boundaries. Finally, when the generalized model was used to predict failure times beyond 5000 hours (using only the shorter test times), the new generalized model had better predictive capability at most temperatures.